2009
DOI: 10.1158/1541-7786.mcr-08-0393
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde Dehydrogenase 1 Is a Tumor Stem Cell-Associated Marker in Lung Cancer

Abstract: Tumor contains small population of cancer stem cells (CSC) that are responsible for its maintenance and relapse. Analysis of these CSCs may lead to effective prognostic and therapeutic strategies for the treatment of cancer patients. We report here the identification of CSCs from human lung cancer cells using Aldefluor assay followed by fluorescence-activated cell sorting analysis. Isolated cancer cells with relatively high aldehyde dehydrogenase 1 (ALDH1) activity display in vitro features of CSCs, including … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
612
4
9

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 709 publications
(654 citation statements)
references
References 36 publications
29
612
4
9
Order By: Relevance
“…ALDH1A1 is a predominant isoform of aldehyde dehydrogenase family in mammals located in the cytoplasm 15,16 and is originally considered as a marker for normal hematopoietic progenitor cells, 17 and is also found in cancer cells with stem cell property, that is, cancer stem-like cells, in several malignant tumors including leukemia, 9 breast cancer 7 and lung cancer. 8,18 Wang et al 19 reported that ALDH1A1 was located in the nuclei of esophageal squamous cell carcinoma cells. However, we detected that ALDH1A1 protein mainly in the cytoplasm of precancerous and cancer cells of esophagus, consistent with reports on breast and ovarian tumors.…”
Section: Discussionmentioning
confidence: 99%
“…ALDH1A1 is a predominant isoform of aldehyde dehydrogenase family in mammals located in the cytoplasm 15,16 and is originally considered as a marker for normal hematopoietic progenitor cells, 17 and is also found in cancer cells with stem cell property, that is, cancer stem-like cells, in several malignant tumors including leukemia, 9 breast cancer 7 and lung cancer. 8,18 Wang et al 19 reported that ALDH1A1 was located in the nuclei of esophageal squamous cell carcinoma cells. However, we detected that ALDH1A1 protein mainly in the cytoplasm of precancerous and cancer cells of esophagus, consistent with reports on breast and ovarian tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Su et al 20 reported that high ALDH1 expression was associated with poor prognosis for patients with bladder urothelial carcinoma and was an independent predictor for cancer-specific survival. Various studies have reported that immunohistochemically identified tumor ALDH1 expression is associated with a poor prognosis in breast, 16,22 lung, 23 and pancreatic 19 cancer patients. Conversely, ALDH1 has a favorable function in ovarian carcinoma and high expression of ALDH1 is a favorable prognostic factor in patients with ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Aldehyde dehydrogenase 1(ALDH1) is a cytosolic isoform of ALDH, and high levels of its activity are seen not only in hematopoietic stem/ progenitor cells but also in solid cancers (eg, breast, 16,17 colorectal, 18 pancreas, 19 bladder 20 and prostate 21 cancers). Furthermore, expression of ALDH1 is a predictor of poor clinical outcome in the breast, 16,22 lung, 23 pancreatic 19 and bladder 20 cancers. Sex determining region-Y-related high mobility group box (SOX) 2 is a transcription factor that is involved in the maintenance of embryonic stem cell pluripotency and in multiple developmental processes.…”
mentioning
confidence: 99%
“…3 Lung cancer stem cells (LCSCs) have been previously identified through different criteria including surface expression of CD133, c-kit or through functional properties such as selective drug survival, elevated aldehyde dehydrogenase (ALDH) activity, increased glycolysis and glycine/serine metabolism or low concentrations of reactive oxygen species and ATP. [4][5][6][7][8][9] Importantly, when inoculated into immunocompromised mice, LCSCs give rise to xenografts that histologically reproduce the tumor of origin, thus representing an improved model for in vivo testing of new targeted therapies. 10 Several tumors express elevated levels of anti-apoptotic Bcl-2 family proteins such as Bcl-2, Bcl-X L and Mcl-1, which affect the apoptotic threshold of neoplastic cells contributing to chemotherapy resistance.…”
mentioning
confidence: 99%